2010
DOI: 10.1186/1756-0500-3-260
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for the detection of biofilm production in coagulase-negative staphylococci

Abstract: BackgroundThe ability of biofilm formation seems to play an essential role in the virulence of coagulase-negative staphylococci (CNS). The most clearly characterized component of staphylococcal biofilms is the polysaccharide intercellular adhesin (PIA) encoded by the icaADBC operon. Biofilm production was studied in 80 coagulase-negative staphylococci (CNS) strains isolated from clinical specimens of newborns with infection hospitalized at the Neonatal Unit of the University Hospital, Faculty of Medicine of Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
98
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 47 publications
13
98
1
2
Order By: Relevance
“…[12,13] A total 169 isolates of Enterobacteriaceae were tested for biofilm production by tube adherence method which can be indicated for the routine detection of biofilm production because of its easy application and low-cost and because it guarantees reliable results with excellent sensitivity and specificity. [14,15] In our study, 59.2% of the tested organisms have shown the potential to make biofilms in comparison to similar study [16] which reported 54%.…”
Section: Discussionmentioning
confidence: 47%
“…[12,13] A total 169 isolates of Enterobacteriaceae were tested for biofilm production by tube adherence method which can be indicated for the routine detection of biofilm production because of its easy application and low-cost and because it guarantees reliable results with excellent sensitivity and specificity. [14,15] In our study, 59.2% of the tested organisms have shown the potential to make biofilms in comparison to similar study [16] which reported 54%.…”
Section: Discussionmentioning
confidence: 47%
“…The CRA method due to its easiness and good sensitivity has been widely used for phenotypic detection of biofilm production in different bacteria (21). In the present study, 54.4% and 70.8% of S. aureus and S. epidermidis isolates were recognized as biofilm producer by CRA method, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…Oliveira and Cucha confirmed the relatively high efficiency of the microplate method [21]. Analysis of 100 CoNS strains isolated from clinical specimens obtained from newborns and tested with the method described by Christensen et al , showed that 46% of isolated were characterized by strong phenotypic capacity for biofilm production, while 35% of them were weak biofilm producers.…”
Section: Resultsmentioning
confidence: 90%
“…Medical implants contaminated by biofilm-forming bacteria may lead to the development of inflammatory foci where implant removal is frequently the only effective treatment of such infections [19,20,21]. Since Staphylococci are part of the resident microbiological flora of the skin the presence of the biofilm-forming strains among them may be associated with an increased risk of transmission of virulent biofilm-forming strains in the hospital environment.…”
Section: Introductionmentioning
confidence: 99%